Prevalence of Iron Deficiency Anemia and its Biochemical Parameters among the Selected School- going Under-priviledged Children in Dhaka City (Journal of Medicine, 2014)
Iron deficiency is a serious health complication particularly in developing countries, which is usually caused due to poor nutrition, genetic disorders and chronic infections. Compared to developed countries prevalence of anaemia in developing and underdeveloped countries is very high, and children are the ones which are mostly affected. In this paper an attempt has been made to study the prevalence of anaemia among some school-going children in Dhaka. An attempt has also been made to assess the severity of anaemia and iron status among the school-going underprivileged children by measuring serum iron (SI), serum TIBC and serum ferritin (SF) and explore a relationship between haemoglobin level and various parameters of iron nutrition. A substantial number of indicators have been used in determining the iron deficiency.Results obtained from the study show that two thirds of the study children are anaemic due to haemoglobin level below 12 gm/dl. However, majority of them had mild anaemia (haemoglobin level between 10.0 to 11.9 gm/dl) and only a few of them had moderate anaemia (haemoglobin level between 7.0 to 9.9 gm/dl). None of the study population had severe anaemia (haemoglobin level below 7.0 gm/dl). Results also show that only 10 of the study population (6%) were found to have significantly low serum iron, low serum ferritin and high serum iron binding capacity (TIBC) as compared to that of the students who had normal haemoglobin level.DOI: http://dx.doi.org/10.3329/jom.v14i2.19657 J Medicine 2013, 14(2): 130-134